The establishment of in vitro culture and drug screening systems for a newly isolated strain of Trypanosoma equiperdum - Suganuma, Keisuke (Int J Parasitol Drugs Drug Resist, 2017)
Dourine is caused by Trypanosoma equiperdum via coitus with an infected horse. Although dourine is distributed in Equidae worldwide and is listed as an internationally important animal disease by the World Organization for Animal Health (OIE), no effective treatment strategies have been established. In addition, there are no reports on drug discovery, because no drug screening system exists for this parasite. A new T. equiperdum strain was recently isolated from the genital organ of a stallion that showed typical symptoms of dourine. In the present study, we adapted T. equiperdum IVM-t1 from soft agarose media to HMI-9 liquid media to develop a drug screening assay for T. equiperdum. An intracellular ATP-based luciferase assay using CellTiter-Glo reagent and an intracellular dehydrogenase activity-based colorimetric assay using WTS-8 tetrazolium salt (CCK-8 reagent) were used in order to examine the trypanocidal effects of each compound. In addition, the IC(50) values of 4 reference trypanocidal compounds (pentamidine, diminazene, suramin and melarsomine) were evaluated and compared using established assays. The IC(50) values of these reference compounds corresponded well to previous studies involving other strains of T. equiperdum. The luciferase assay would be suitable for the mass screening of chemical libraries against T. equiperdum because it allows for the simple and rapid-evaluation of the trypanocidal activities of test compounds, while a simple, inexpensive colorimetric assay will be applicable in developing countries for the evaluation of the drug sensitivity of epidemic trypanosome strains.